The Integration of Ethnoscience and Technology: A Review - Yusof, Norazmie; Yaqin, Lalu Nurul; Pg Aliudin, Pg Mohd Rahiman; Mahali, Saidatul Nornis (International Journal of Ethnoscience and Technology in Education, 2024)
This literature review critically examines the integration of ethnoscience and technology, highlighting the transformative impact of this amalgamation on the field of social sciences. Ethnoscience, with its focus on understanding the diverse ways in which human communities perceive and interact with their world, and ethnography, a methodology for the immersive study of cultures and social interactions, together provide a robust framework for exploring human cognition, behavior, and societal constructs. The review delves into the key principles of ethnoscience, emphasizing the development and significance of ethnography in anthropological research and the methodological flexibility required to address contemporary challenges. This study further explores the integration of technological innovations such as wearables, digital traces, and information and communication technology (ICT) into ethnographic studies, underscoring the opportunities and challenges presented by the digital era. The paper argues that the incorporation of technology not only expands the methodological toolkit available to researchers but also enhances the depth and breadth of ethnographic insights into socio-economic, policy, and environmental factors influencing technology adoption across various sectors. Despite the methodological, socio-economic, and infrastructural hurdles, the integration offers unprecedented opportunities for understanding complex social phenomena, contributing significantly to policy-making, community development, and technological innovation. This review underscores the necessity of evolving ethnographic practices to keep pace with technological advancements, fostering a deeper and more nuanced understanding of the intricacies of human life in the digital age.